Extension of the Poincaré Symmetry and Its Field Theoretical Implementation - Tanasa, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We define a new algebraic extension of the Poincaré symmetry; this algebra is used to implement a field theoretical model. Free Lagrangians are explicitly constructed; several discussions regarding degrees of freedom, compatibility with Abelian gauge invariance etc. are done. Finally we analyse the possibilities of interaction terms for this model.